Особливості брендингу Apple: мовний та візуальний аспекти - Каратаєва, М.В. (Лінгвістика ХХІ століття: нові дослідження і перспективи, 2012)
The article deals with language and visual features of Apple Inc. branding. It studies the evolution of logotype and peculiarities of combination of visual and verbal information in the texts of print, video and virtual advertising. It regards the role of text creolization and the use of rhetorical and visual means as contributory factors of pragmatic effect and argumentation.